Notes on a small collection of phaneropterine bush-crickets (Insecta: Orthoptera: Tettigonioidea) from Central and Southern Madagascar with the description of two new species - Heller, Klaus-Gerhard; Hemp, Claudia; Massa, Bruno; Rakotondranary, Jacques; Krištín, Anton (Zootaxa, 2019)
During a joint ecological project of the Institute of Forest Ecology, Slovak Academy of Sciences, Zvolen, Slovakia, and the University of Antananarivo, Madagascar, eight species (10 specimens) of phaneropterine bush-crickets were collected. Among them, two species were found as new to science (Mimoscudderia longicaudata n. sp., Paraphyrrhicia leuca n. sp.) and are described in this paper. Two other species (Plangia segonoides, Trigonocorypha maxima) were found the first time after their description more than 100 years ago. We provide first detailed data about their localities and habitat.